The thread unraveled: the great themes of traditional popular music in Brazil - Monteiro, Marianna F. M.; Dias, Paulo (Estudos Avançados, 2010)
In the Brazilian popular chants, dances and festivities one can detect different motifs and patterns of a tissue. It is interesting to investigate and follow each of these threads that constitute this weft, grouping them according to their texture or coloring. These different thematic lines, threads of the weft of artistic and religious expressions of the Brazilian people are the theme of this article, which intends to analyze cultural forms characterized by hybridization which often resides in the ambiguity between resistance and acceptance of a dominant cultural pattern. The dynamism of these arrangements makes us speculate about the formation or constitution of these artistic practices, as well as their circulation, trying to investigate about the processes that were responsible for the broadcasting of these characteristics and similarities in such an enormous country.